Role interleukin 18 in the course and progression of osteoarthritis in patients with obesity - Anastasiia Litvynova (Bogomolets National Medical University, 2022)
musculoskeletal disorders are an extremely common pathology. They are the most common cause of chronic pain and disability: every minute, more than 30% of adults suffer from joint pain or limited physical activity. These diseases significantly affect the psychosocial status of patients, their families, and caregivers. The course of joint diseases leads to loss of mobility, social autonomy; such patients have higher rates of hospitalization and mortality. That is, the quality of life significantly deteriorates, and the financial costs of health care for patients and society increase. It is proved that one of the predictors of arthrosis is overweight. In the pathogenesis of osteoarthritis and obesity, proinflammatory cytokines play an important role, the excess synthesis of which leads to the progression and chronicity of the process. Therefore, the aim of our study was to determine the dependence of interleukin-18 activity in patients with osteoarthritis, which occurs on the background of obesity and without it. The study presents the study of interleukin-18 in 75 people with osteoarthritis (OA), which occurred on the background of obesity (main group), and 50 patients with isolated OA (comparison group). The control group consisted of 37 healthy individuals. The diagnosis of OA was established based on the order of the Ministry of Health of Ukraine of 12.10.2006 "On medical care for patients with osteoarthritis", unified diagnostic criteria of the Association of Rheumatologists of Ukraine (2004), and the criteria of the American College of Rheumatologists. The presence and severity of obesity were assessed according to the criteria of the International Diabetes Federation (IDF, 2005) based on the calculation of body mass index (BMI) according to the Kettle formula. When determining the level of IL-18 in the main group, it was found that the content of this cytokine was almost two times higher than the reference values (p <0.05). In the comparison group, the activity of IL-18 increased 1.6 times (p <0.05). Comparison of the content of IL-18 between the study groups allowed us to determine its increase in the presence of obesity by almost 1.2 times. The increase in IL-18 content depended on the radiological stage of joint damage: the maximum value was recorded in patients of the main group with stage 2 symptoms. Apparently, such results are a consequence of the predominance of the inflammatory reaction in the progression of the pathology due to the comprehensive involvement of extra-articular components (ligaments, tendons, bags, etc.). Slightly lower levels of IL-18 in stage 1 OA are likely to be due to the involvement of a limited portion of joint tissue, while the 3rd radiological stage is characterized by a predominance of dystrophic processes. In patients with osteoarthritis, an increase in the content of IL-18 in the serum is determined, which is associated with the development of the inflammatory process in the components of the joint. The content of IL-18 has a direct correlation with overweight / obesity and the radiological stage of the process in the joints. Increased proinflammatory cytokine IL-18, which is a component of the immune system and simultaneously synthesized by adipocytes of adipose tissue, can be considered a factor that will contribute to the preservation of chronic pain and progression of the pathology. Dynamic control of IL-18 activity should be used as an indicator of the effectiveness of therapy.